If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6t=5t+4
We move all terms to the left:
6t-(5t+4)=0
We get rid of parentheses
6t-5t-4=0
We add all the numbers together, and all the variables
t-4=0
We move all terms containing t to the left, all other terms to the right
t=4
| 1/n=-1 | | H=t+4 | | 3(j-9)+1=19 | | 2(d-11)-4=4 | | k(7k+2)=5 | | 14x+64=6x-64 | | 16=12z-100 | | 12x+32=-6x-32 | | x-5=+2 | | 3p+1=9+4p | | 9x-35=6x+43 | | 3*j=27 | | 24n=22 | | 24=22n | | 3x+6+153=180 | | -w=-9+2w | | 2x+3=9(9) | | 3m-113=-115 | | 1=2-y | | 3x+16+7x-10+2x+6=180 | | -8s-10=2s | | -10x+3x-2=180 | | 4x-1+2x-7+5x+1=180 | | -10x+3x-2=189 | | 9x-(2x+4)=3x-32 | | 7j2−6j−9=0 | | 4x-3x=-3x+20 | | 10x-2=360 | | 3q2+8q+3=0 | | 26-b=8 | | –5x-20=15-10x | | 32=-6s+4 |